Active Studio Experiences in Architectural Design Education - Yurtsever, Bengi; Polatoglu, Cigdem (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2020)
In today's world, where everything is easily and frequently replicated, that which is unique is disappearing. These circumstances change the point of view of the individual regarding design and create a society that seeks and prefers uniformity, devalues what is unusual or different, and does not encourage or develop original, distinctive ideas. The environment is a reflection of the architectural approach and the prevailing thinking. The present study examines this scenario in the context of the educational dimension of architectural design and assesses these issues using a discovery process of constant change. Generation, experience, and meaning given to difference, space, place, atmosphere, and their components were examined to analyze the effect of cognitive differences and the value of originality in relation to the environment. An inverted approach was used, focused on alternative learning environments and participant interaction. To contrast a process with structured, stratified views, contemporary learning approaches were applied as the foundation of this study: a constructivist, embedded, qualitative research formula. The issues were explored from within the architectural design studio experience. An active studio concept based on experiences was used, incorporating personalized and constructivist ideas generated using blended learning and an inverted methodology. In this approach, the hypothesis of the study is not a static problem. Instead, it is flexible and organic, renewed in every new environment. The network of relationships among studio members, which reveals the field of experience, generates the initial formulation. The questions and problems identified in the first studio experience are the basis for new hypotheses, and create a different, second studio environment. The active studio experience, because it is dynamic and involves questioning what currently exists, is an environment that animates and inspires individual exploration. It fosters the ability to genuinely be involved in the flow of the moment and, without force, do what the moment requires, rather than simple, directed activity that does not explore beyond the present standard. In order to see the comprehensive, long-lasting experience environment, all three of these studio experiences were evaluated, including consideration of: -Sharing -Suggestion development -Responsibility -Volunteering -Communication These elements were measured after the studio experience according to the analysis of the structure and findings, including participant interaction. The active studio should be seen as an environment that adapts to the present and continues to flow with it, not as a differentiated environment. This could be considered a process of recovery. Given the increasing number of architecture students and the growth of academic departments, blended media provide a valuable addition or alternative. The rigid structure of today's environment and architectural design studios have the potential to be active and truly creative in essence.
Keywords: Active studio; Architectural design education; blended learning; constructivist grounded theory; studio culture; Architecture